Peran Zakat dalam Pendidikan Masyarakat Islam: Ulasan Kasus Zakat Pulau Pinang - Zakaria Bahari (Media Syari'ah, 2017)
Zakat is one of the instruments in Islamic economics which play roles to increase a socio-economic development of Islam in general and asnaf in particular. The increase in socio- economic policy needs to include recipients, especially the poor and needy recipients. Among the most important as well as the need to eat, shelter and clothing, education is also very important because education can enhance the capabilities of the poor and needy recipients as well as the Muslim community in order to improve the factors of production out of mustahiq and become to muzzaki. Which problems in recipients of zakat funds for education do? How does the distribution of zakat funds to education can be done by the management of zakat institutions to the target group intended? What conclusion can be made to the role of the Board of Zakat Pulau Pinang (ZPP) for its contribution to education in Penang? Methods in implementing this writing, is to use secondary data and content analysis. Therefore, this article aims to examine the appropriate recipients for the distribution of zakat in education. Second, identify program implementation zakat management education institutions in Penang and eventually formulate ZPP role in contributing to education. Research findings tell us that zakat distribution for educational purposes basically through pi sabilillah asnaf. However, the programs were implemented by the Penang Zakat Management in dissemination the education of the Muslim community is not only through asnaf pi sabilillah, but also through poor and needy asnaf, ghoramin and mualaf (conversion). Conclusion the zakat contributions relating to education given to asnaf to enhance the syiar of Islam and closer to Allah SWT, especially to educational activities through formal education, preaching, counseling, training / courses, management and administration.